Deviant Behavior of Children in Social Media from Perspective of Law and Criminology: Does Creativity on Social Media Encourage Bad Behavior in Children? (Journal of Creativity Student, 2022)
Juvenile delinquency is a phenomenon that is often studied from a social, psychological, and legal perspective. In principle, children have different handling characteristics. For example, in legal studies, children have unique and distinctive procedures, starting from the Juvenile Criminal Justice System, Child Criminal Law, and Child Protection. However, along with the development of increasingly open technology and information, deviant behaviors in children continue to develop. This study aims to analyze how children's deviant behavior in social media in the study of law and criminology. The method used in this study is a mixed method between empirical and normative studies. This method is used to answer substantially the rules regarding child deviance on social media and the protection provided for children, as well as to see facts and phenomena directly in the field regarding child deviance on social media and some of the factors behind it. This study uses a legal and criminological study approach. The location of this research was specifically carried out in the city of Semarang, and several other cities as supporting material. Supporting data in this study were also obtained from various studies on the internet. This research was submitted through the DIPA Student Research grant scheme, Faculty of Law, Semarang State University in 2022. The outputs in this study consisted of mandatory and additional outputs. The mandatory output in this research is in the form of articles published in the National Journal, while additional outputs are in the form of book designs and/or Copyrights. This research was conducted by a team that has the capacity in their field, in addition, this research is the initiation of increasing publications carried out by the Student Journal Team of the Faculty of Law, Semarang State University.